The corrosion resistance of heatproof nickel alloy in molten fluoride salts - Azhazha, V.M.; Bakai, A.S.; Bobrov, Yu.P.; Virich, V.D.; Yemlyaninova, T.G.; Kapustin, V.L.; Kovtun, K.V.; Lavrinenko, S.D.; Malykhin, D.G.; Petel’guzov, I.A.; Pylypenko, M.M.; Savchenko, V.I.; et al. (Вопросы атомной науки и техники, 2005)
Studies have been made into corrosion and mechanical properties of high-nickel alloys prepared at NSC KIPT on the basis of high-purity metal components. Corrosion tests of the Hastelloy-type alloy in fluoride melts at 650°C revealed formation of no films in the process of corrosion during 700 hours. The corrosion of the alloy under study in molten fluorides is characterized by a weak interaction of melt components with the alloy, by penetration of Zr and Na atoms into the alloy at a depth of 3 to 5 μm over 700 hours, by the absence of oxide films on the surface. The chromium content in the near-surface layer of the alloy decreases to a depth of 10 μm. Corrosion tests cause no essential changes in the mechanical properties of the alloy.